Optimization of extraction methods for characterization of phenolic compounds in apricot fruit (Prunus armeniaca). Issue 10 (19th September 2019) - Iglesias-Carres, Lisard; Mas-Capdevila, Anna; Bravo, Francisca Isabel; Bladé, Cinta; Arola-Arnal, Anna; Muguerza, Begoña
Abstract : Fruits are rich in phenolic compounds with health-promoting activities. Abstract : Fruits are rich in phenolic compounds with health-promoting activities. However, phenolic profiles vary between fruits. Hence, specific extraction methods are required for accurate profiling of the functional compounds. This study aims to develop an optimised method by response surface methodology to extract phenolics from apricots ( Prunus armeniaca ) and correctly characterise apricots' phenolic profile. For this, the effects of the solid-to-liquid ratio, temperature, extraction solvent, extraction time and sequential extraction steps on the extraction of major phenolic families were investigated. Methanol- and ethanol-based extractions were suitable, although methanol was the optimal solvent. The optimised extraction conditions were 20 g mL −1, 38 °C and 72% methanol (1% formic acid). When this method was used in apricots, the characterisation of their phenolic profile by HPLC-ESI-MS/MS showed a higher extraction of phenolic compounds than other studies in the literature that use non-specific extraction methods. The developed method is fast and economically feasible for accurate characterisation of the phenolic profile of apricot fruits and thus can be routinely used to extract apricot phenolic compounds for their characterisation.